Charakterystyka zużycia wody w systemach wodociągowych "Wilków" i "Borek" w gminie Głogów = Characteristics of water consumption in water supply systems "Wilków" and "Borek" in Głogów commune - Ogiołda, Ewa; Kozaczek, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water consumption is an important parameter of water sypply system. Analysis of values measured during 16 years exploitation in 2 systems gave possibility to calculate coefficients of unit demand and water consumption irregularity during one day, week and year.
Keywords: system zaopatrzenia w wodę; zapotrzebowanie na wodę; zużycie wody; water supply system; water demand; water consumption